Effect of yoga based techniques on stress and health indices using electro photonic imaging technique in managers - Kushwah, Kuldeep K. (J Ayurveda Integr Med, 2016)
BACKGROUND: Meditation techniques are known to elicit relaxation response in which moving meditation which combines the practice of yoga postures and guided relaxation is known as Cyclic Meditation reported helpful in reducing the sympathetic arousal and improving health of practitioners. OBJECTIVES: The objective of this study was to investigate the effect of Cyclic Meditation on stress and health indices in managers as measured by Electro Photonic Imaging (EPI) technique. MATERIALS AND METHODS: EPI technique was used to assess participants before and after 35 min of Cyclic Meditation (CM) and equal duration of Supine Rest (SR) session. A total of sixty six male managers, age ranges from 35 to 60 years (mean ± SD 53.97 ± 5.96) were included in the study. EPI parameters, including Activation Coefficient, Integral Area left and right and Integral Entropy, left and right were taken for statistical analyses. RESULTS: Cyclic Meditation has produced a highly significant reduction in stress level, whereas this reduction was not found significant within SR group. There was a significant improvement in health index ‘Integral Area’ values in both left and right sides within the CM group while only IA right side showed a significant improvement within the CM group. The integral entropy value right side decreased significantly within the CM group, whereas IE left was found deteriorated within the SR group. Moreover, only IE left side has shown a significant difference between the groups. CONCLUSION: The investigations in this study suggest that Cyclic Meditation practice reduces stress and improves psychosomatic health indices more effectively than Supine Rest in managers.